AB0311 HEMOSTASIS IN AFRICAN BLACK COMPARED TO WHITE PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Robinson, Chanel; Tsang, Linda; Solomon, Ahmed; Woodiwiss, Angela; Norton, Gavin; Hsu, Hon-Chun; Mer, Mervyn; Millen, Aletta; Dessein, Patrick
Abstract : Background: Aberrant hemostasis is implicated in the increased CVD risk experienced by patients with rheumatoid arthritis (RA) (1). Large circulating concentrations of plasminogen activator inhibitor-1 (PAI-1) predict cardiovascular event rates (2). PAI-1 levels are markedly smaller in American and African black populations than in those of European descent (3, 4). Whether this protection persists in black persons who have RA is unknown. Objectives: This study compared hemostasis factors among African black and white RA patients Methods: PAI-1, tissue factor pathway inhibitor (TFPI) and tissue plasminogen activator (t-PA) levels were measured by ELISA in 236 (114 black; 122 white) African RA patients. Data were analysed in mixed regression models. Results: In age and sex adjusted analysis, PAI-1 concentrations were larger in black compared to white patients with RA (median (interquartile range (IQR))=12.4 (3.1-28.7) versus 5.4 (1.5-25.0) ng/ml, p=0.006). In all patients, body mass index (BMI) (β (SE)=0.022 (0.007), p=0003), waist circumference (β (SE)=0.007 (0.003), p=0.04) and tetracycline use (β (SE)=0.291 (0.133), p=0.03) were associated with logarithmically transformed PAI-1 levels. Population grouping did not influence these relationships (interaction p>/=0.8) but impacted rheumatoid factor (RF) positivity- and azathioprine use-PAI-1 level associations (interaction p=0.03 and 0.004, respectively). In stratified analysis, RF positivity was associated with PAI-1 levels in white (β (SE)=0.344 (0.139), p=0.01) but not black patients (β (SE)=-0.102 (0.143), p=0.5), and azathioprine use was associated with PAI-1 levels in black (β=0.400 (0.155), p=0.01) but not white patients (β (SE)=0.305 (0.184), p=0.1). In age, sex, BMI, RF positivity and azathioprine and tetracycline use adjusted analysis, black population origin remained associated with PAI-1 levels (β (SE)=0.175 (0.091), p=0.05). In age and sex adjusted analysis, TFPI and t-PA levels did not differ in black compared to white RA patients (median (IQR)=221.0 (149.8-410.5) versus 225.0 (130.4-357.2) pg/ml, p=0.6, and 6.7 (4.9-9.1) versus 7.4 (4.4-10.0) pg/ml, p=0.3). Conclusion: PAI-1 concentrations are substantially larger in African black compared to white patients with RA. References: [1] Van den Hoever IAM, Sattar N, Nurmohamed MT. Thromboembolic and cardiovascular risk in rheumatoid arthritis: role of the haemostatic system. Ann Rheum Dis 2014;73:954-7. [2] Jung RG, Motazedian P, Ramirez FD, et al. Association between plasminogen activator-1 and cardiovascular events: a systematic review and meta-analysis. Thrombosis J (2018) 16:12. [3] Festa A, D'Agostino R, Rich SS, et al. Promoter (4G/5G) plasminogen activator inhibitor-1 genotype and plasminogen activator inhibitor-1 levels in blacks, Hispanics and non-Hispanic whites. The Insulin Resistance Atherosclerosis Study. Circulation 2003;107:2422-7. [4] De Lange Z, Rijken DC, Hoekstra T, et al. In black South Africans from rural and urban communities, the 4G/5G PAI-1 polymorphism influences PAI-1 activity, but not plasma clot lysis time. PLoS One 2013;8 (12): e83151. Disclosure of Interests: None declared